Genomic evaluation of residual feed intake in US Holstein cows: insights into lifetime feed efficiency - Khanal, P.; Johnson, J.; Gouveia, G.; Utsunomiya, A.T.H.; Ross, P.; Deeb, N. (Frontiers in Genetics, 2024)
Residual feed intake (RFI) is an important feed efficiency trait that has been increasingly considered in breeding objectives for dairy cattle. The objectives of this study were to estimate the genetic parameters of RFI and its component traits [dry matter intake (DMI), body weight (BW) and energy corrected milk (ECM)] in lactating Holstein cows, to develop a system for genomic evaluation for RFI in lactating Holstein cows and to explore the association of RFI of heifers and cows. RFI was calculated from 2,538 first (n = 2,118) and second (n = 420) lactation Holsteins cows between 2020 and 2024 as part of STgenetics EcoFeed® program. There were 1,516 animals with previous RFI as heifers from the same research station. After quality control, 61,283 single nucleotide polymorphisms were used for the analyses. Univariate analyses were performed to estimate the heritabilities for RFI and its components in lactating cows, and bivariate analyses were performed to estimate the genetic correlation between RFI of heifer and lactating cow using genomic best unbiased linear prediction (GBLUP) method. Animals with phenotypes and genotypes were used as training population and animals with only genotypes were considered as prediction population. Reliability of breeding values was obtained by approximation based on partitioning a function of the accuracy of training population genomic estimated breeding values (GEBVs) and magnitudes of genomic relationships between individuals in the training and prediction population. The heritability estimates (mean ± SE) of RFI, DMI, ECM, and BW, were 0.43 ± 0.07, 0.44 ± 0.04, 0.40 ± 0.05, and 0.46 ± 0.04, respectively. Average reliability of GEBVs for RFI from training and prediction population were 44% and 30%, respectively. The genetic correlations for RFI were 0.42 ± 0.08 between heifer and first lactation cows and 0.34 ± 0.06 between heifer and, first and second lactation cows. Our results showed that genetic component of RFI is not fully carried over from heifers to cows and there is re-ranking of individuals at different life stages. Selection of animals for feed efficiency on a lifetime basis requires accounting for efficiencies during animal growth and milk production as a lactating cow.